Title Regulatory Strategy for Utilizing Augmented Reality as a Visual Aid in Science Learning in Rural Elementary Schools - Karim, Fibriyanti; Uno, Winda Anggriyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This study examines the integration of Augmented Reality (AR) as a visual aid in science learning at rural elementary schools in Indonesia. Rural schools face limited access to digital media and weak infrastructure, creating barriers for students in understanding abstract scientific concepts. The aim of this research is to formulate a regulatory strategy that supports sustainable AR adoption in rural education. A mixed methods sequential exploratory design was used. The quantitative phase involved a survey of 90 respondents (45 teachers and 45 students) to identify readiness and barriers. The qualitative phase included interviews with teachers, principals, and education officials, as well as analysis of local and national education policy documents. Findings reveal that the main obstacles include poor internet access (78%), lack of teacher training (72%), and limited AR devices (68%). A small-scale trial in two schools showed a significant improvement in student learning outcomes, with average test scores increasing from 65.2 to 78.5 (t(54)=6.72, p<0.001). The study concludes that a four-pillar regulatory framework—comprising infrastructure and access, teacher capacity building, curriculum alignment, and monitoring & evaluation—is essential to enable equitable and sustainable AR integration. This framework provides practical recommendations for policymakers and contributes to advancing digital inclusion in rural education.